INTRODUCTION OF DIGITAL MARKETING TO INCREASE THE SALES POWER OF MSMEs IN SUKOMAKMUR VILLAGE - Yahya Nur Hidayat (Institut Agama Islam Syubbanul Wathon Magelang, 2023)
This community service activity which was carried out on July 31 2023 has the aim of assisting digital marketing activities in Sukomakmur Village, Magelang Regency. The form of assistance is carried out in the form of socialization which is carried out at the Sukomakmur village hall, Kajoran District. The material presented is related to the introduction of digital marketing, the benefits of branding, social media, brand naming, icons, when to post, how to provide watermarks and recommendations for applications to use to make the product more attractive. In community service, a business registration number, halal certification and digital marketing workshop was held with 20 participants from Sukomakmur Village, including Marongan Hamlet, Gunung Malang Hamlet, Nampan Hamlet, Krandegan Hamlet, Gendol Hamlet, Naden Hamlet. The training stage consists of several activities including: (1) introduction to Digital Marketing and branding. (2) introduction to social media. (3) introduction of the marketplace. To carry out this socialization, lecture, discussion and practice methods were used. Socialization is carried out to provide an understanding of digital concepts, social media and the benefits of using social media. Apart from that, assistance is provided to improve technical capabilities for content on platforms such as: Tik-tok, Instagram and Facebook. The results of the evaluation of digital marketing training activities show that this activity received a positive response, was assessed as being able to provide new knowledge and knowledge, and received responses that provided inspiration for MSMEs in Sukomakmur village.